KEMAMPUAN GURU DALAM PROSES BELAJAR MENGAJAR MATA PELAJARAN ILMU PENGETAHUAN SOSIAL TERPADU MATERI INTERAKSI SOSIAL - Huda, Fatkhan Amirul; Thoharudin, Munawar (STKIP Persada Khatulistiwa Sintang, 2019)
Abstract: The purpose of this study was to find objective information about the ability of teachers in the teaching and learning process of Integrated Social Sciences subjects in the social interaction class VII in SMP Negeri 4 Dedai 2018/2019 Academic Year. The research method is descriptive method, the form of research is descriptive analysis. The population in this study where students of grade VIII of 24 students. Data collection techniques using direct observation techniques, direct communication, indirect communication, and study documentation. Based on the results of teacher and student interviews conducted shows that the learning process carried out has been effective and efficient. Efforts to overcome the obstacles in the process of teaching and learning include teachers understanding student characteristics, understanding the components of the method of evaluation and understanding the environmental conditions in learning. Based on the results of research in general about the ability of teachers in the teaching and learning process of Integrated Social Sciences subjects on the subjects of social interaction are categorized as good.Keywords: Teacher’s Ability, Teaching and Learning Process.Abstrak: Tujuan penelitian ini adalah untuk mengetahui informasi yang objektif mengenai kemampuan guru dalam proses belajar mengajar mata pelajaran Ilmu Pengetahuan Sosial Terpadu pada matari interaksi sosial kelas VII di SMP Negeri 4 Dedai Tahun Pelajaran 2018/2019. Metode penelitian yaitu metode deskriptif, bentuk penelitian adalah deskriptif analisis. Populasi penelitian adalah siswa kelas VII sebanyak 24 siswa. Teknik pengumpulan data menggunakan teknik observasi langsung, komunikasi langsung, komunikasi tidak langsung, dan studi dokumentasi. Berdasarkan hasil wawancara guru dan siswa yang dilakukan menunjukan bahwa proses pembelajaran yang dilakukan telah efektif dan efisien. Upaya mengatasi faktor hambatan dalam proses belajar mengajar antara lain guru memahami karakteristik siswa, memahami komponen metode dengan evaluasi dan memahami kondisi lingkungan dalam belajar. Berdasarkan hasil penelitian secara umum tentang kemampuan guru dalam proses belajar mengajar mata pelajaran Ilmu Pengetahuan Sosial Terpadu pada matari interaksi sosial dikategorikan baik.Kata Kunci: Kemampuan Guru , Proses Belajar Mengajar